Gut Microbiota Shifting in Irritable Bowel Syndrome: The Mysterious Role of Blastocystis sp. - Olyaiee, Alireza; Sadeghi, Amir; Yadegar, Abbas; Mirsamadi, Elnaz Sadat; Mirjalali, Hamed (Frontiers in Medicine, 2022)
Irritable bowel syndrome (IBS) is a chronic disorder, which its causative agent is not completely clear; however, the interaction between microorganisms and gastrointestinal (GI) epithelial cells plays a critical role in the development of IBS and presenting symptoms. During recent decades, many studies have highlighted the high prevalence of Blastocystis sp. in patients with IBS and suggested a probable role for this protist in this disease. Recent studies have documented changes in the gut microbiota composition in patients with IBS regarding the presence of Blastocystis sp., but it is not clear that either disturbance of the gut during GI disorders is a favorable condition for Blastocystis sp. colonization or the presence of this protist may lead to alteration in the gut microbiota in IBS patients. In this review, we comprehensively gather and discuss scientific findings covering the role of Blastocystis sp. in IBS via gut microbiota shifting.